2014
DOI: 10.2134/agronj14.0075
|View full text |Cite
|
Sign up to set email alerts
|

Stocker Steer Performance on Tall Fescue or Meadow Fescue Alone or in Binary Mixture with White Clover

Abstract: Little research has been conducted in the northern United States to evaluate meadow fescue [Schedonorus pratensis (Huds.) P. Beauv] or tall fescue [S. arundinaceus (Schreb.) Dumort] in pastures, and implications for animal performance. is research compared swards containing meadow fescue (MF) or tall fescue (TF) alone or co-established with white clover (Trifolium repens L.). Pastures were rotationally grazed with crossbred beef steers (Bos taurus, initial weight 261 kg, n = 180) using a variable stocking rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 29 publications
2
17
3
Order By: Relevance
“…Contrary to hypotheses and studies of forage nutritive value (Sleugh et al, 2000;Schaefer et al, 2014), cattle grazing legume-interseeded pastures did not have greater dietary CP concentrations compared with N-fertilized pastures, and neither dietary CP nor NDF concentrations varied by season. Cattle grazing legume-interseeded pastures had 11% less dietary NDF and 5% greater dung N concentrations than cattle grazing N-fertilized pastures.…”
Section: Dietary Nutritive Value and Dung Qualitycontrasting
confidence: 91%
See 1 more Smart Citation
“…Contrary to hypotheses and studies of forage nutritive value (Sleugh et al, 2000;Schaefer et al, 2014), cattle grazing legume-interseeded pastures did not have greater dietary CP concentrations compared with N-fertilized pastures, and neither dietary CP nor NDF concentrations varied by season. Cattle grazing legume-interseeded pastures had 11% less dietary NDF and 5% greater dung N concentrations than cattle grazing N-fertilized pastures.…”
Section: Dietary Nutritive Value and Dung Qualitycontrasting
confidence: 91%
“…Similar dietary CP and NDF concentrations, dung N concentrations, and dung C/N ratios in June and August indicated cattle likely maintained selection of similar dietary grass/ legume ratios in the legume-interseeded pastures and leaf proportions in N-fertilized pastures despite expected changes in grass maturity (Buxton, 1990;Ferdinandez and Coulman, 2001) and legume proportions (Sleugh et al, 2000;Schaefer et al, 2014) across the growing season. Similar dietary CP and NDF concentrations, dung N concentrations, and dung C/N ratios in June and August indicated cattle likely maintained selection of similar dietary grass/ legume ratios in the legume-interseeded pastures and leaf proportions in N-fertilized pastures despite expected changes in grass maturity (Buxton, 1990;Ferdinandez and Coulman, 2001) and legume proportions (Sleugh et al, 2000;Schaefer et al, 2014) across the growing season.…”
Section: Dietary Nutritive Value and Dung Qualitymentioning
confidence: 97%
“…In contrast, legumes were grazed more frequently than expected. These results are consistent with two prior studies conducted in twospecies pastures containing tall fescue and either alfalfa (Medicago sativa (L.); Boland et al, 2012) or white clover (Schaefer et al, 2014), which showed that cattle prefer legumes when grazing in legume-tall fescue mixtures. Our results extend these findings, demonstrating this pattern in heterogeneous pastures containing many more forage species.…”
Section: Discussionsupporting
confidence: 92%
“…Unfortunately, despite the resilience and grazing potential of diverse‐forage pastures (Sanderson, Goslee, & Soder, ; Soder et al., ), few data are available on cattle selectivity for tall fescue versus other forages in such systems. To date, research has focused on the preferences of steers for tall fescue versus legumes in two‐species systems, finding that steers consume more legumes than tall fescue and achieve greater weight gain as a result (Boland et al., ; Schaefer, Albrecht, & Schaefer, ). Although to our knowledge, there are no reports on selectivity with respect to tall fescue in pastures with higher plant diversity, cattle have been shown to frequently graze warm‐season grasses (e.g., switchgrass Panicum virgatum (L.), big bluestem Andropogon gerardii (Vitman)) relative to their availability during the summer, while grazing cool‐season grasses (e.g., Kentucky bluegrass Poa pratensis (L.)) disproportionately less (Plumb & Dodd, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation